2020
DOI: 10.1002/bit.27320
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic skin chip with vasculature for recapitulating the immune response of the skin tissue

Abstract: There is a considerable need for cell‐based in vitro skin models for studying dermatological diseases and testing cosmetic products, but current in vitro skin models lack physiological relevance compared to human skin tissue. For example, many dermatological disorders involve complex immune responses, but current skin models are not capable of recapitulating the phenomena. Previously, we reported development of a microfluidic skin chip with a vessel structure and vascular endothelial cells. In this study, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 51 publications
0
46
0
Order By: Relevance
“…Metabolic parameters and change of skin tissue over time have been monitored in this platform. Recently, Kwak et al [133] fabricated a skin-on-a-chip microfluidic platform in which epidermal and dermal layers were co-cultured with human umbilical vascular endothelial cells. Immune responses such as an increase in secretion of cytokines and migration of neutrophils into the demal layer after exposure to doxorubicin and UV irradiation have been observed.…”
Section: Skinmentioning
confidence: 99%
“…Metabolic parameters and change of skin tissue over time have been monitored in this platform. Recently, Kwak et al [133] fabricated a skin-on-a-chip microfluidic platform in which epidermal and dermal layers were co-cultured with human umbilical vascular endothelial cells. Immune responses such as an increase in secretion of cytokines and migration of neutrophils into the demal layer after exposure to doxorubicin and UV irradiation have been observed.…”
Section: Skinmentioning
confidence: 99%
“…These studies showed synovial fibroblasts from patients with rheumatoid arthritis increased the number of neutrophils adhering to endothelial cells compared to their healthy counterparts. Recently, a device incorporating a flat endothelium, fibroblasts in a sub-luminal collagen gel, and a keratinocyte monolayer was developed (139). Using this model, Kwak et al demonstrated ultraviolet lightinduced cytokine secretion by the resident cells increased neutrophil TEM.…”
Section: Neutrophil-fibroblast Interactionsmentioning
confidence: 99%
“…12 A useful prioritization of MPS applications can be found in Table 1 of the review by Watson, Hunziker, and Wikswo, 2017. 10 Currently, there are MPS of nearly every major human organ 20 including liver, 16,41 vasculature, 42,43 blood-brain barrier (BBB), [44][45][46] skeletal [47][48][49] and cardiac muscle, [50][51][52][53][54][55][56][57] kidney, [58][59][60][61] female reproductive tissues (uterus, cervix, fallopian tubes), 62 testes, 63 brain, 37,64 skin, [65][66][67] gut, 40 bone, 68 and eye. 69,70 Specific MPS organ systems have also been linked to form multi-organ systems to more accurately depict systemic responses to a variety of drugs and therapeutics.…”
Section: Impact Statementmentioning
confidence: 99%